Emerging Biomarkers for Monitoring of Glucocorticoid Replacement Therapy in Congenital Adrenal Hyperplasia (CAH) - Bresnahan, Lauren (Auckland University of Technology, 2023)
Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder involving an enzyme defect which affects adrenal steroid synthesis. The incidence is approximately 1 in every 20,000 births, and early intervention and treatment is crucial in severe cases. It is currently screened for as part of the national newborn metabolic screening program at LabPlus, Auckland Hospital. Reduced enzyme function leads to cortisol and aldosterone deficiency, in addition to androgen excess. There is a wide spectrum of disease severity; it causes virilisation of external genitalia, and the most severe forms can be life-threatening due to risk of salt wasting in the neonatal period. Patients are given lifelong replacement steroid therapy to counteract these effects and must undergo regular monitoring to maintain treatment balance. The main laboratory biomarker currently used for treatment monitoring, 17-hydroxyprogesterone (17-OHP), is not ideal as it is a steroid metabolite, not an active androgen, which may be influenced by several factors. This study aims to investigate new androgenic steroids which have emerged in the last few years as being of importance in CAH patients and determine whether they have the potential to provide further information about the clinical status of CAH patients undergoing glucocorticoid therapy. Method development and validation was performed using liquid chromatography mass spectrometry to investigate the viability of measuring 11-ketoandrostenedione, 11-hydroxyandrostenedione, 11-ketotestosterone, and 11-hydroxytestosterone in dried blood spots. Dried blood spots are the current sample type for newborn screening and monitoring of CAH patients in New Zealand. All four steroids demonstrated suitable intra-batch precision and linearity, but 11-ketoandrostenedione proved less reproducible than the others across the course of validation. The results of the validation indicate that at least three of the four steroids show promise for future work on the assessment of treatment monitoring for patients with CAH who are undergoing glucocorticoid therapy. In addition, there are other areas of clinical interest where this analysis could be adopted, for example polycystic ovary syndrome, adrenal tumours, and the doping industry.